Pendidikan Optimisme dalam Islam: Kajian Makna Optimisme dalam Perspektif Teori Self-Esteem - Purahman1; Moh. Khoirul Umam (Institut Kariman Wirayudha Sumenep, 2024)
Modern human life tends to be influinced by negagatife experiences, giving rose to despair, depression and disappointmen in living life. This is not permitted in Islam. This research aim to answer this problem through and agreed approach to optimism in the verses of the Qur’an using the perspctive of self-esteem theory. Thi research uses a literature study approach with the main data in the form of verses from the Al-Qur’an, interpretations and expert opinion abput optimistic character education in jurnal, books, and study result. The conclusion of this research is that Islam introduces education optimism with terms, namely as-shabru, la tahzanu, la tay’asu, and la taqnathu. Meanwhile, self-esteem theory emphasizes giving assesment, appreciation, and good things to on self. The theory of self-esteem has a correlation with the term Islamic optimism which know onself (ya’rif an-nafs), recognize human perfection (insanul kamil), and appreciate to know onself (yardhaun an-nafs). The character education context of optimism as-shobru, la tahzanu, la tay’asu, and la taqnathu develops human abilities to assess objectively and respon conditional wisely and positively so as to know weaknesses and strengths, which ultimately encourages humans to konw Good mor Far. So tha the concept Islamic oftimism education forms a positive human charater that can emerge from negative things such as depression, disappointment and frustration that can be the cause of mental destruction.